Revealing the impact of teaching methods on anxiety among college students through a bibliometric study - Ai, Zhongzhu; Yuan, Dongfeng; Dong, Ruotong; Li, Yun; Zhou, Shanshan (Frontiers in Psychology, 2025)
ObjectiveAnxiety has become increasingly prevalent among university students, significantly affecting their academic performance. Reforming teaching methods as a potential strategy to alleviate anxiety has garnered growing attention over the years. This study aims to systematically analyze and discuss the impact of teaching method reforms on college student anxiety.MethodsThe Web of Science (WOS) database was used to retrieve and collect relevant literature from 2004 to 2024. Major publication sources, countries, institutions, and authors in this field were identified through the number of publications, citation frequency, and H-index indicators. Data-driven analysis was conducted to explore collaboration patterns, knowledge structures, research hotspots, and trends using VOSviewer software.ResultsAfter screening, this study included 192 publications from January 2004 to November 2024, revealing several significant findings: (1) The number of publications has gradually increased, peaking in 2022 and maintaining a high level in the following years. (2) The most productive and influential journals are Nurse Education Today and CBE Life Sciences Education, with the USA and the Indiana University System contributing the most. (3) Collaboration network analysis indicates the presence of multiple research groups in the field, but their connections among countries and authors remain relatively limited. (4) Co-citation analysis of journals shows that the field is interdisciplinary, primarily merging psychology, education, and information technology. (5) Keyword analysis identifies two major research hotspots: factors influencing student anxiety in teaching environments (e.g., self-efficacy, loneliness, and performance) and the moderating effects of teaching method reforms (e.g., blended learning, collaborative learning, and experiential learning) on college student anxiety.ConclusionThis visualization analysis provides an overview of the directions and advancements in research on the impact of teaching method reforms on college students' anxiety. It offers a comprehensive examination of the latest frontiers and trends, contributing theoretical support to educational practices and mental health interventions.